2021
DOI: 10.37897/rjn.2021.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio is modality to predict recurrence, disability and mortality of ischemic stroke following acute phase

Abstract: Stroke has been known as the second greatest cause of mortality and the third cause of disability. Ischemic stroke is more frequent than hemorrhagic stroke. The pathophysiology of ischemic stroke relates with inflammatory process. Neutrophil and lymphocyte are part of that process. Routine peripheral hematological laboratory, which contains information of neutrophil and lymphocyte, is easy, cheap and rapid test. This literature review purposes to explain the modality of neutrophil-lymphocyte ratio (NLR) in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The research ndings suggest that a high NLR can negatively affect long-term results. In a study on AIS patients byWirawan and Widyadharma (2021), it was demonstrated that high NLR following the acute phase of the event could adversely affect long-term outcomes, such as the recurrence of ischemic stroke, morbidity, and mortality. Additionally,Majid et al (2021) have reported that in patients with acute ischemic stroke receiving thrombolysis treatment, high NLR values are associated with poor functional outcomes after three months.…”
mentioning
confidence: 99%
“…The research ndings suggest that a high NLR can negatively affect long-term results. In a study on AIS patients byWirawan and Widyadharma (2021), it was demonstrated that high NLR following the acute phase of the event could adversely affect long-term outcomes, such as the recurrence of ischemic stroke, morbidity, and mortality. Additionally,Majid et al (2021) have reported that in patients with acute ischemic stroke receiving thrombolysis treatment, high NLR values are associated with poor functional outcomes after three months.…”
mentioning
confidence: 99%